Visual Consultation Method Of Information Technology - Yizhan, Yao (2005)
In this dissertation a method, called IT_VCM or Visual Consultation Method of Information Technology is presented, it is a visual, based-templete consulting methodology from qualitative hypothesis to quantitative validation.